Research on Rail Grinding Technology of Medium and Low Speed Based on Specific Grinding Energy - Jie LIU; Tao ZHENG (机车电传动)
In order to improve the efficiency of rail grinding, according to the existing machining and grinding principles of machine tools and the calculation method of high-speed cutting specific grinding energy, the application research of precision control technology for medium and low speed rail grinding was carried out. Taking the standard 60N rail profile grinding as an example, the geometric features of the profile surface were extracted and divided into four grinding areas. According to the empirical relationship between the rail pre-grinding profile surface ratio grinding energy and the amount of grinding, the empirical calculation model of the grinding amount of the rail profile surface is established, and the feasibility and accuracy of the calculation model were verified through on-site grinding tests. The results showed that after three grinding calculations, the maximum grinding amount of rail head profile area 2 was 7.28 mm2, and the minimum grinding amount of area 3 was 1.18 mm2, and the total cutting amount of the on-site grinding test was relative to the theoretical calculation. The deviations were -3.57% and -4.24%, respectively, and the total grinding results were consistent with the rail grinding accuracy requirements.